2019
DOI: 10.1016/j.buildenv.2019.106276
|View full text |Cite
|
Sign up to set email alerts
|

Indoor comfort and adaptation in low-income and middle-income residential buildings in a Nigerian city during a dry season

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
3
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 20 publications
3
17
3
1
Order By: Relevance
“…More than two-thirds of urban dwellers in Nigeria were not satisfied with their thermal environment, according to research (M. U. Adaji et al 2019). Furthermore, the results of this investigation have confirmed that the lack of thermal well-being of the inhabitants affects their sanitary conditionand it was found that they suffer from chronic morbidities (allergy, rheumatism, diabetes, tension).…”
Section: Assessment Of the Thermal Well Being Of Collective Residenti...mentioning
confidence: 55%
“…More than two-thirds of urban dwellers in Nigeria were not satisfied with their thermal environment, according to research (M. U. Adaji et al 2019). Furthermore, the results of this investigation have confirmed that the lack of thermal well-being of the inhabitants affects their sanitary conditionand it was found that they suffer from chronic morbidities (allergy, rheumatism, diabetes, tension).…”
Section: Assessment Of the Thermal Well Being Of Collective Residenti...mentioning
confidence: 55%
“…However, some authors analyzed a specific aspect that characterizes the IEQ. For example, the authors of [ 56 ] examined the thermal comfort of occupants during the dry season in low- and middle-income residential buildings in Abuja, Nigeria. In the study, post-occupancy surveys were used to assess the adaptation of buildings and residents’ adaptation to the thermal environment.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies identified the prevalence of, and increase in, thermal discomfort and actual heat stress within low-income settings in the selected African countries. In their post-occupancy evaluation of low-income housing in Abuja (Nigeria), with a hot and humid climate, Adaji et al [25] showed that over 70% of the occupants were dissatisfied with their thermal environment. The average temperature in their case study settings was 31.7 • C. In Ibadan, Adegebo [26] found that 43% of the 400 survey respondents agreed that there is a "warmer/hotter temperature during day and night" over the preceding five years.…”
Section: Experiences and Perceptions Of (Increasing) Thermal Discomfo...mentioning
confidence: 99%